Modelagem e processamento de dados sísmicos 2D - SANTOS FILHO, João Batista (2020)
The main objective of this TCC report was to develop a complete flowchart for modeling and processing of seismic reflection data aimed at the reconstitution of a subsurface geological model. The maim steps consisted of: (1) design of a geological model based on publications of coastal sedimentary basins; (2) discretization of the model for a spatial window (depth, length), and the temporal window; (3) organization of the data cube; (4) conventional seismic processing. The techniques used follow a flowchart pre-established and carried out from a make le that works as an organizer of the modeling and processing steps. This work was performed on desktop under Linux, and on the Seismic Unix developed by the Central Wave Phenomena (CWP) of the Colorado School of Mines. It was also used the software PROMAX of the LandMark company installed in the machines of the seismic processing laboratory - PROSIS, as academic licences.